2009
DOI: 10.3109/08916930903374683
|View full text |Cite
|
Sign up to set email alerts
|

The biology of reactive intermediates in systemic lupus erythematosus

Abstract: Systemic lupus erythematosus (SLE) is an autoimmune syndrome marked by autoantibody production. Innate immunity is essential to transform humoral autoimmunity into the clinical lupus phenotype. Nitric oxide (NO) is a membrane-permeable signaling molecule involved in a broad array of biologic processes through its ability to modify proteins, lipids, and DNA and alter their function and immunogenicity. The literature regarding mechanisms through which NO regulates inflammation and cell survival is filled with co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
56
1
4

Year Published

2011
2011
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(61 citation statements)
references
References 60 publications
0
56
1
4
Order By: Relevance
“…Interestingly, despite the reduction in NO production, iNOS protein levels were not reduced in the 17-DMAG-treated immune-stimulated cells. We would expect iNOS expression to be reduced with suppression of NF-jB translocation [45,61]. While we did observe reduced NF-jB translocation with 17-DMAG treatment in immune-stimulated cells, we did not find a reduction in iNOS expression, suggesting that inhibiting NF-jB translocation may not be sufficient to down-regulate iNOS expression.…”
Section: Discussioncontrasting
confidence: 54%
See 1 more Smart Citation
“…Interestingly, despite the reduction in NO production, iNOS protein levels were not reduced in the 17-DMAG-treated immune-stimulated cells. We would expect iNOS expression to be reduced with suppression of NF-jB translocation [45,61]. While we did observe reduced NF-jB translocation with 17-DMAG treatment in immune-stimulated cells, we did not find a reduction in iNOS expression, suggesting that inhibiting NF-jB translocation may not be sufficient to down-regulate iNOS expression.…”
Section: Discussioncontrasting
confidence: 54%
“…NO production can be induced by immune stimulation [61]. Recently it was shown that HSP70 can function as an inhibitor of iNOS [62].…”
Section: Discussionmentioning
confidence: 99%
“…As occurs with other autoimmune diseases, inflammation and oxidative stress are frequent in the course of SLE (3,4). According to this, some authors have reported higher levels of the biomarker of inflammation, C-reactive protein (CRP), in these chronic patients compared to controls (4)(5)(6).…”
Section: Introductionmentioning
confidence: 84%
“…Al-Griw et al Open Veterinary Journal, (2016), Vol. 6(3): 150-157 reported in various diseases (Khan et al, 2001;Morgan et al, 2005;Oates, 2010;Wang et al, 2013). Proteins perform crucial functions within living cells, but even a relatively minor structural modification of proteins often leads to a marked change (generally lowering) in their functions (Orengo et al, 1999).…”
Section: Introductionmentioning
confidence: 99%